Effect of temperament on milking behavior and milk yield in Surti buffaloes (Indian Journal of Animal Production and Management, 2024)
Present study was conducted on twenty-three Surti buffaloes maintained at Livestock Research Station  under Navsari Agricultural University, Navsari, Gujarat with the objective to study the general temperament  and its effect on milking behaviour traits and milk yield. Important milking behavioural traits like total  milking time, milk flow rate and milk yield per milking were recorded at the time of each milking. All of  these parameters were recorded on day 6 postpartum thereafter at fortnight interval till 90th postpartum.  The collected data were compiled, tabulated and analyzed by using SAS 9.2. Perusal of data revealed  that during early lactation temperament of primiparous buffaloes found to be restless-nervous type. The  temperament score was significantly higher (p
Keywords: Milking behavior; Milk yield; Surti buffalo; Temperament